Impaired fish swimming performance following dietary exposure to the marine phycotoxin okadaic acid. (May 2020) - Corriere, Mauro; Baptista, Miguel; Paula, José R.; Repolho, Tiago; Rosa, Rui; Costa, Pedro Reis; Soliño, Lucía
Abstract: Fish are frequently exposed to harmful algal blooms (HAB) and to related toxins. However, the biological effects of okadaic acid (OA), the most abundant and frequent HAB-toxin in Europe, South America and Asia, have been poorly investigated. In this study, fish swimming performance and metabolic rates were investigated in juveniles of Zebra seabream ( Diplodus cervinus ) exposed to OA-group toxins via dietary route, during three days. Fish fed on contaminated food accumulated up to 455.5 μg OA equiv. Kg −1 . Significant lower mean critical swimming speed ( Ucrit ) were observed in fish orally exposed to OA (and its related isomer dinophysistoxin-1, DTX-1) than fish feeding on non-toxic diet. A tendency to higher demands of oxygen consumption was also recorded in OA-exposed fish at higher current velocities. This study indicates that fish may not be affected by OA-group toxins under basal conditions, but suggests a decrease in fitness linked to a reduction in swimming performance of fish exposed to OA under increased stimulus. OA and related toxins are suggested to have a cryptic effect on swimming performance that may be enhanced when fish deals with multiple stressors. Considering that a reduction in swimming performance may have impact on critical activities, such as foraging and escaping from predators, this study highlights the ecological risk associated with dinoflagellate toxic blooms, biotoxins food web transfer and fish contamination. Highlights: Fish fed an okadaic acid (OA)-enriched diet exhibited lower metabolic fitness. Reduced swimming performance was observed in fish fed an OA-enriched diet. 7-O-acyl derivatives of OA and dinophysistoxin-1 were not detected in fish fed an OA-enriched diet.